ETIKA EKOLOGIS DALAM AL-QUR’AN: KAJIAN TAFSIR MAUDHUI TERHADAP PRINSIP KONSERVASI DAN KESEIMBANGAN LINGKUNGAN HIDUP - Muhammad Faris; Muhammad Fazryn; Muhammad Panji (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This study examines the principles of ecological ethics in the Qur’an through a thematic interpretation (tafsīr maudhū‘ī) approach. The research aims to explore Qur’anic values that form the moral and theological foundation for human responsibility toward the environment. By analyzing relevant verses alongside classical and contemporary exegeses, the study identifies key ethical principles such as khilāfah (stewardship), mīzān (balance), prohibition of fasād (corruption or destruction), and qanā‘ah (moderation). These principles emphasize that environmental preservation is not merely a social obligation but an integral part of faith and worship. The findings highlight that Qur’anic ecological ethics provide a spiritual framework for addressing modern environmental crises and promoting sustainable living rooted in divine harmony.